2017
DOI: 10.1136/rmdopen-2016-000384
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in early systemic sclerosis

Abstract: Objectives(1) Hypothesis testing of the potency of rituximab (RTX) in preventing fibrotic complications and (2) assessing acceptability and feasibility of RTX in early systemic sclerosis (SSc).MethodsA small, 24-month, randomised, double-blind, placebo-controlled, single-centre trial in patients with SSc diagnosed <2 years was conducted. Patients received RTX or placebo infusions at t=0, t=15 days and t=6 months. Patients were clinically evaluated every 3 months, with lung function tests and high-resolution CT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
49
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 46 publications
0
49
0
5
Order By: Relevance
“…We excluded 42 studies (Abou-Raya, A., 2013 [ 29 ]; Allanore, Y., 2018 [ 30 ]; Allanore, Y., 2019 [ 31 ]; ASSET, 2019 [ 32 ]; ASSIST, 2011 [ 33 ]; Boonstra, M., 2017 [ 34 ]; Chakravarty, E.F., 2015 [ 35 ]; Daoussis, D., 2010 [ 36 ]; Daoussis, D., 2012 [ 37 ]; Daoussis, D., 2017 [ 38 ]; Denton, C., 2007 [ 39 ]; EDITA, 2019 [ 40 ]; FaSScinate, 2016 [ 41 ]; FocuSSced, 2020 [ 42 ]; Gordon, J.K., 2018 [ 43 ]; Gruber, B.L., 1991 [ 44 ]; Guillevin, L., 1982 [ 45 ]; Guo, H.M., 2008 [ 46 ]; Henes, J., 2020 [ 47 ]; Herrick, A.L., 2017 [ 48 ]; Hoffmann-Vold, A.M., 2019 [ 49 ]; Khanna, D., 2009 [ 50 ]; Khanna, D., 2019 [ 50 ]; Mehrabi, S., 2019 [ 51 ]; Nadashkevich, O., 2008 [ 52 ]; NCT02283762 [ 53 ]; NCT02465437 [ 54 ]; NCT02745145 [ 55 ]; Pakas, J., 2002 [ 56 ]; Panopoulos, S.T., 2013 [ 57 ]; Poormoghim, H., 2013 [ 58 ]; Pope, J.E., 2001 [ 59 ]; Prey, S., 2012 [ 60 ]; Quillinan, N.P., 2014 [ 61 ]; Schiopu, E., 2016 [ 62 ]; Sclero XIII, 2019 [ 63 ]; Seibold, J.R., 2000 [ 64 ]; Seibold, J.R., 2010 [ 65 ]; Su, T.I.K., 2009 [ 66 ]; Sullivan, A., 2018 [ 67 ]; van den Hoogen, F.H.J., 1996 [ 68 ]; van Laar, J.M., 2014 [ 69 ]). Reasons for exclusion are described in the Supplementary material 2.1, pages 25–26 .…”
Section: Resultsmentioning
confidence: 99%
“…We excluded 42 studies (Abou-Raya, A., 2013 [ 29 ]; Allanore, Y., 2018 [ 30 ]; Allanore, Y., 2019 [ 31 ]; ASSET, 2019 [ 32 ]; ASSIST, 2011 [ 33 ]; Boonstra, M., 2017 [ 34 ]; Chakravarty, E.F., 2015 [ 35 ]; Daoussis, D., 2010 [ 36 ]; Daoussis, D., 2012 [ 37 ]; Daoussis, D., 2017 [ 38 ]; Denton, C., 2007 [ 39 ]; EDITA, 2019 [ 40 ]; FaSScinate, 2016 [ 41 ]; FocuSSced, 2020 [ 42 ]; Gordon, J.K., 2018 [ 43 ]; Gruber, B.L., 1991 [ 44 ]; Guillevin, L., 1982 [ 45 ]; Guo, H.M., 2008 [ 46 ]; Henes, J., 2020 [ 47 ]; Herrick, A.L., 2017 [ 48 ]; Hoffmann-Vold, A.M., 2019 [ 49 ]; Khanna, D., 2009 [ 50 ]; Khanna, D., 2019 [ 50 ]; Mehrabi, S., 2019 [ 51 ]; Nadashkevich, O., 2008 [ 52 ]; NCT02283762 [ 53 ]; NCT02465437 [ 54 ]; NCT02745145 [ 55 ]; Pakas, J., 2002 [ 56 ]; Panopoulos, S.T., 2013 [ 57 ]; Poormoghim, H., 2013 [ 58 ]; Pope, J.E., 2001 [ 59 ]; Prey, S., 2012 [ 60 ]; Quillinan, N.P., 2014 [ 61 ]; Schiopu, E., 2016 [ 62 ]; Sclero XIII, 2019 [ 63 ]; Seibold, J.R., 2000 [ 64 ]; Seibold, J.R., 2010 [ 65 ]; Su, T.I.K., 2009 [ 66 ]; Sullivan, A., 2018 [ 67 ]; van den Hoogen, F.H.J., 1996 [ 68 ]; van Laar, J.M., 2014 [ 69 ]). Reasons for exclusion are described in the Supplementary material 2.1, pages 25–26 .…”
Section: Resultsmentioning
confidence: 99%
“…Как правило, в эти исследования включались больные с диффузной формой ССД на ранней стадии, когда индурация кожи является доминирующим симптомом. Исключениями можно считать два небольших исследования (оба с группами сравнения без лечения), в которых изменений плотности кожи (по модифицированному кожному счету Роднана) между группами не было [5,29]. активности было ожидаемым изменение СОЭ и СРБ, которые изначально были повышенными, хотя и умеренно.…”
Section: Discussionunclassified
“…84 The double-blind RCT study by Boonstra M et al also examined 16 early (<2years disease duration) scleroderma patients. 82 Patients treated with Rituximab showed moderately improvement, although not statistically significant, of lung function compared to patients on placebo. Skin score did not differ between groups.…”
Section: Mycophenolate Mofetil Mycophenolate Mofetil (Mmf)mentioning
confidence: 91%
“…Skin score did not differ between groups. 82 On the contrary, Thiebaut M et al in their retrospective study of 53 patients (13 from a single centre in France combined with data from 40 additional patients retrieved from published cases) concluded that RTX improves skin, and lung function. 83 Currently RTX is considered in cases with worsening ILD following treatment with CyP.…”
Section: Mycophenolate Mofetil Mycophenolate Mofetil (Mmf)mentioning
confidence: 98%
See 1 more Smart Citation